Psychoanalyse und Justiz - Moser, Tilmann; Reik, Theodor; Alexander, Franz; Staub, Hugo (Suhrkamp-Taschenbuch, 1974)
Reik, T. Geständniszwang und Strafbedürfnis.--Alexander, F. und Staub, H. Der Verbrecher und seine Richter